2021
DOI: 10.1002/csr.2175
|View full text |Cite
|
Sign up to set email alerts
|

The level of sustainability and mutual fund performance in Europe: An empirical analysis using ESG ratings

Abstract: Over recent years, investors' attention on the environment, social responsibility, and governance (ESG) has been growing. At the same time, managers, investors, and regulators are interested in ascertaining whether mutual funds that invest in ESG‐compliant assets perform better than those with a low ESG commitment. The sustainability of funds' portfolios can be measured by ESG ratings, a measure of the financially material ESG factors of the securities held by a fund. Our study therefore aims to verify whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…The first one is the large complexity of manifesting corporate social responsibility amid the COVID-19 crisis. During a crisis, companies face a deficit of resources even for supporting their main activities, while corporate social responsibility, which belongs to additional activities and is financed according to the leftover principle even in the period of stability, becomes almost inaccessible for business management-at least, in the traditional form, which supposes limited opportunities for the return of social investments of business, especially during a crisis (Abate et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first one is the large complexity of manifesting corporate social responsibility amid the COVID-19 crisis. During a crisis, companies face a deficit of resources even for supporting their main activities, while corporate social responsibility, which belongs to additional activities and is financed according to the leftover principle even in the period of stability, becomes almost inaccessible for business management-at least, in the traditional form, which supposes limited opportunities for the return of social investments of business, especially during a crisis (Abate et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Friede et al (2015) conducted a study on ESG/SRI factors and found a significant positive relationship between ESG performance and financial performance. Abate et al (2021) shows that fund portfolio composed with high ESG-rating securities performed better that low ESG-compliant counterparts.…”
Section: Discussion Of the Utaut For Integration Of Esg Information I...mentioning
confidence: 95%
“…He reported that the two classes of mutual funds do not differ statistically in the characteristics of assets they hold, in diversification, or in overall performance. In constrast, a similar study [1] on European mutual funds reports a superior "efficiency" of funds that focus on high ESG rated securities. Giese et al [39] studied ESG causality on (as opposed to "correlation with") financial performance by considering transmission channels of systematic and idiosyncratic risk within a standard discounted cash flow model, through which ESG ratings data (specifically MSCI ESG ratings data) impact valuation and performance.…”
Section: Introductionmentioning
confidence: 90%